Research map in education and Pedagogy of graduates and its social impact - Villacrez Oliva, María Victoria (SATHIRI, 2023)
Education requires pedagogical transformations that allow the reflection of the research processes carried out by the graduates, from the different areas of knowledge; thus, in the self-evaluation processes of the programs, it is essential to understand the importance of the investigative pedagogical practice. This article presents the results of a research work, where 86 research projects of the Bachelor’s program in Basic Elementary’s graduates from Universidad Mariana are analyzed, to determinate the social scope and propose a map of investigative trends that glimpse the relevant issues in our region from the perspective of territory, to propose a comprehensive description that allows a reading towards the configuration of regions and research trends. In this sense, from the explored works, they were deduced recurring themes, opacities, coordinates, theories, impacts on the region, geographical importance and the competences of the graduates for their development. Its methodological design is quantitative because it uses the collection and analysis of data to establish patterns of behavior in a population; in terms of the empirical-analytical approach, it is relevant to the study because it enables the review of the survey, interview and analytical review to establish relevances and opacities. Besides, the type of descriptive research allowed consolidating all the findings through an interpretation where the results are presented with a theoretical construction that strengthens their understanding and that made it possible to glimpse a regional geography in relation to education and pedagogy from the perspective of the impact of the investigations.